Соціальні ризики реформи децентралізації - Zelenkevich, Liana; Зеленкевич, Ліана; Зеленкевич, Лиана (Східноєвропейський національний університет імені Лесі Українки, 2019)
У роботі розкрито проблематику визначення соціальних ризиків, які наявні в процесі реформи децентралізації. Актуальність такого дослідження зумовлена необхідністю передбачення соціальних ризиків від створення ОТГ, проведення секторальної децентралізації тощо, аби запобігти або пом’якшити можливих негативних наслідків від їх реалізації. Представлено авторське поняття соціальних ризиків децентралізації як ситуацій, викликаних реформою децентралізації, які загрожують соціальному добробуту, соціальному самопочуттю, існуванню й подальшому розвитку сільської громади та впливають на суспільство загалом. Спираючись на результати соціологічного дослідження, проведеного LLC «MLS group», дані офіційного моніторингу децентралізації й інші матеріали, ми зробили висновок про можливість виокремлення таких соціальних ризиків децентралізації, як ризик надмірної концентрації землі в приватній власності владних осіб або аграрних бізнесменів; ризик порушення земельних прав простих селян; ризик виникнення невдоволення селян об’єднанням у спільну громаду та ін. In the paper, the present-day risks of decentralization reform are considered at the theoretical and empirical levels, which is carried out today for economic reasons, in order to create capable communities. The author argues that the decision of an economic nature, in the framework of decentralization, has social consequences, the risks of deteriorating social climate, and social mood of the population. The author's definition of the social risks of decentralization, which refers to situations or activities caused by the decentralization reform, which threaten social well-being, social well-being, the existence and further development of the rural community, and affect society as a whole. According to the author, such risks have four features of sociality: 1. in terms of content – it is a risk of violations of social well-being and well-being; 2. At risk – this is a risk to communities; 3. The origin of risk is the decentralization reform; 4. For social significance, it is important for the community and society as a whole. Based on the results of a sociological survey conducted by LLC «MLS group», official monitoring of decentralization and other materials, the author came to the conclusion that it is possible to distinguish the following social risks of decentralization: the risk of excessive concentration of land in private ownership of the authorities or agrarian oligarchs; etc. In addition to this, the creation of an UTC can become another means of exploiting the countryside city. There is a risk of neglect by the interests of non-centered communities. There are also risks of worsening social comfort for residents of non-central communities in connection with the closure of social infrastructure in small villages. The authorities propose the timely adoption of measures that would prevent the emergence of negative consequences of the implementation of reforms in the countryside.
Social Risks of Decentralization Reform
Keywords: село; місцева влада; громадська думка; уповільнення реформи; об’єднана територіальна громада; село; местные власти; общественное мнение; замедление реформ; объединенная территориальная община